2022
DOI: 10.1126/sciadv.abn9889
|View full text |Cite
|
Sign up to set email alerts
|

Foraging complexity and the evolution of childhood

Abstract: Our species’ long childhood is hypothesized to have evolved as a period for learning complex foraging skills. Researchers studying the development of foraging proficiency have focused on assessing this hypothesis, yet studies present inconsistent conclusions regarding the connection between foraging skill development and niche complexity. Here, we leverage published records of child and adolescent foragers from 28 societies to (i) quantify how skill-intensive different resources are and (ii) assess whether chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…It is unlikely, however, that young girls collected food items as efficiently as adult women. We observed that BaYaka children often practiced digging wild yams or cracking nuts, but the amount that they collected would hardly match that of the women enough to offset the foraging cost of nursing women, as gathering requires a high level of skill and strength [ 38 40 ]. Instead, girls may reduce the burden of childcare for nursing women by holding, monitoring and playing with nursing children while their mothers work, as they were observed to do in camp ([ 6 , 13 , 21 , 26 , 32 , 33 ]; but see [ 14 ]).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely, however, that young girls collected food items as efficiently as adult women. We observed that BaYaka children often practiced digging wild yams or cracking nuts, but the amount that they collected would hardly match that of the women enough to offset the foraging cost of nursing women, as gathering requires a high level of skill and strength [ 38 40 ]. Instead, girls may reduce the burden of childcare for nursing women by holding, monitoring and playing with nursing children while their mothers work, as they were observed to do in camp ([ 6 , 13 , 21 , 26 , 32 , 33 ]; but see [ 14 ]).…”
Section: Discussionmentioning
confidence: 99%
“…We built on existing literature (e.g. [16,20]) to develop a Compared with previous studies, we improve the statistical methodology by not only including a principled treatment of missing data, but also by analysing children's ecological knowledge using IRT, whereby we can maximize the information yielded from different tasks (questions) across a protocol that is necessarily quite difficult to construct. We also provide a structural equation model approach to estimating impacts on productive activity on both individual-and trip-level traits, which can contribute to better controlled investigations into individual-level effects in the future.…”
Section: Discussionmentioning
confidence: 99%
“…non-zero returns) and (ii) the amount of returns (e.g. grams or calories collected) for a certain trip [14,16,20,35]. In the case of the present study, however, the two types of foraging are analysed with just one of the two parts of a hurdle model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence point to delayed maturation of H. erectus individuals, producing a longer juvenile period that is intermediate between earlier hominins and modern humans(Parker, 2000;Antón and Leigh, 2003;Nowell and White, 2010), although this is actively debated(Dean and Smith, 2009). As studies of hunter-gatherer cultural transmission show, childhood is when most teaching and learning occurs(Gurven et al, 2006;Hewlett, 2016;Boyette and Hewlett, 2017), and that long childhoods allow for the learning of ever-more-complex foraging tasks(Pretelli et al 2022). Children can learn through play and devote time to practice before they are expected to contribute signi cantly to foraging tasks.…”
mentioning
confidence: 99%